(untitled) (Global Journal of Human-Social Science, 2024)
This study investigated the benefits of Merlot grape pomace extract (EBUM) in experimental acetaminophen-induced intoxication. Swiss mice received the respective treatments for 7 days: Control (saline), Silymarin (100 mg/Kg), EBUM: 100 mg/Kg and 500 mg/Kg. On the seventh day, the acetaminophen control, Silymarin and EBUM received a single dose of acetaminophen 500 mg/kg. After 24 hours, the mice were sacrificed, the blood and liver were collected for analysis of serum transaminases (ALT and AST), bilirubin, hepatic markers of oxidative stress and histopathological analysis. EBUM was able to prevent acetaminopheninduced hepatic necrosis with a significant reduction (p